Effectiveness of hypofractionated and normofractionated radiotherapy in a triple‐negative breast cancer model - Grosche, Sinja; Bogdanova, Natalia V.; Ramachandran, Dhanya; Lüdeking, Marcus; Stemwedel, Katharina; Christiansen, Hans; Henkenberens, Christoph; Merten, Roland (Frontiers in Oncology, 2022)
Breast cancer (BC) is one of the most diagnosed malignant carcinomas in women with a triple‐negative breast cancer (TNBC) phenotype being correlated with poorer prognosis. Fractionated radiotherapy (RT) is a central component of breast cancer management, especially after breast conserving surgery and is increasingly important for TNBC subtype prognosis. In recent years, moderately hypofractionated radiation schedules are establishing as a standard of care, but many professionals remain skeptical and are concerned about the efficiency and side effects. In the present study two different triple-negative breast cancer cell lines, non-malignant breast epithelial cell line and fibroblasts were irradiated daily under normofractionated and hypofractionated schedules to evaluate the impact of different irradiation regimes on radiation-induced cell-biological effects. During the series of radiotherapy, proliferation, growth rate, double strand DNA break-repair (DDR), cellular senescence and cell survival were measured using typical cell culture procedures. Investigated normal and cancer cells differed in their responses and receptivity to different irradiation regimens, indicating cell line/cell type specificity of the effect. At the end of both therapy concepts, normal and malignant cells reach almost the same endpoint of cell count and proliferation inhibition, confirming the clinical observations in the follow-up at the cellular level. These results in cell lines, closely replicating the irradiation schedules in clinical practice, to some extent, contribute to the understanding of growth rate or remission of tumor and development of fibrosis.